Trends in the Incidence and Survival Outcomes in Patients With Small Cell Lung Cancer in the United States: An Analysis of the SEER Database - Dipesh Uprety; Randell Seaton; Abesh Niroula; Tarik Hadid; Kaushal Parikh; Julie J. Ruterbusch (Cancer Medicine)
ABSTRACT Background There has been a lack of updated epidemiological data on the incidence and survival outcomes for patients with small cell lung cancer (SCLC) in the United States over the last two decades. Methods A retrospective, population‐based study was conducted utilizing the Surveillance, Epidemiology, and End Results (SEER) program to identify patients with SCLC from 2000 to 2020. Trends in cancer incidence, incidence‐based mortality rates, 1‐year relative survival rates and 1‐year observed survival were evaluated utilizing the SEER database. Results The database identified a total of 188,426 SCLC patients during the study period from 2000 through 2020. The age‐adjusted incidence rate slowly declined, on average, by 3% (95% CI: −3.2% to −2.8%) each year from 9 per 100,000 in 2000 to 4.6 per 100,000 in 2020. The decline is evident for all age groups, sexes, and races. Incidence‐based mortality also declined slowly from 6.6 in 2005 to 3.5 in 2020. However, survival outcomes, including 1‐year relative survival and 1‐year observed survivals, have not improved significantly over the last two decades. Conclusion This study found that the incidence of SCLC has decreased from 2000 to 2020, likely due to a reduction in smoking rates, underscoring the importance of smoking abstinence. An improvement in incidence‐based mortality is likely related to an enhanced medical care and a decrease in the incidence of SCLC, but the lack of improvement in survival outcomes reflects the need for more effective systemic therapy.